Strategi Public Relations dalam Pengembangan Brand Image di SD NAIS Bekasi - Qonita Diah Hidayati; Sadiyah El Adawiyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Educational institutions need to have good relations with the surrounding community. To build a good and optimal image of an educational institution, it is necessary to have an open system for communicating and working well with each party. Nurul Amin Elementary School is an educational institution that has an active role in communicating with the community. There is Public Relations which has carried out its duties by building a positive image through social media. Researchers focus on how to develop a Public Relations Strategy, develop a Brand Image and the benefits provided to the community and schools at SD Nurul Amin Islamic School. The research method that the author uses is a qualitative method, using field research. This descriptive qualitative research uses a phenomenological approach. The results of this research are that SD Nurul Amin Bekasi carried out four main steps, namely: First, by carrying out careful planning related to clear programs, in accordance with the objectives. Second, the formation of an organization which is usually called MASMEDIA or the abbreviation for public relations and media. Third, strategic planning is prepared and approved. Implementations designed and prepared by the school include activities, meetings, parenting outing classes, market days, and so on. Fourth, carry out evaluations, by measuring how big the results are after running, as well as accepting criticism and suggestions from the community.